Zombie apocalypse - Frade, B. A. (New York ; Boston : Little, Brown and Company, 2017)
"When their pranks start turning scary and real zombies arrive on the scene, twins Tyler and Ryan must find a way to undo the damage they--and the Tales from the Scaremaster book that seems to be pulling the strings--have caused"--
Keywords: Supernatural -- Fiction; Zombies -- Fiction; Books -- Fiction; Twins -- Fiction; Mystery and detective stories; Detective and mystery stories; Paranormal fiction; Zombies -- Juvenile fiction; Books -- Juvenile fiction; Twins -- Juvenile fiction; Books -- Fiction; Twins -- Fiction; Zombies -- Fiction; Paranormal fiction; Books - Fiction; Zombies - Fiction; Mystery and detective stories; Supernatural - Fiction; Twins - Fiction; Paranormal fiction; Detective and mystery fiction